Privacy Concerns in E-commerce Marketing: A Systematic Literature Review Study - Yao, Hua; Tarofder, Arun Kumar (International Journal of Global Economics and Management, 2024)
The purpose of this research is to undertake a systematic literature view to analyze the current status of privacy concerns in e-commerce marketing context. The study identifies published papers over the past two decades and examines 81 articles extracted from Scopus database using research methodology, descriptive analysis and thematic analysis. In the course of the research, with the rapid development of information technology, shopping online has become an upward trend, it has also resulted in a continuous rise in privacy concerns in e-commerce marketing. Although consumer privacy literature in e-commerce research has gained huge attention, empirical research has tended to inconsistent results in e-commerce. VOSviewer software was adopted as a tool to conduct descriptive analysis and thematical analysis. Based on the synthesis of articles in the existing literature, this study focused on consumer privacy concerns in the context of e-commerce marketing and provides insightful research directions in this domain. The scope of the extracted literature is confined keywords-based research, future research should elaborate on a wider perspective with the combination of Scopus and Web of Science database.